ON THE USE OF «SPEAKING» NAMES IN A LITERARY TEXT - Слободяк, Светлана (SWorldJournal, 2022)
The article deals with the issue of the functioning of "speaking" names in fiction, namely in the plays of the British playwright Richard Brinsley Sheridan "The School for Scandal" and "The Rivals". It is noted that "speaking" anthroponyms in a literary t